2020
DOI: 10.1021/acs.jproteome.0c00581
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Coproduced Extracellular Vesicles in HEK293 during Virus-Like Particle Production

Abstract: Vaccine therapies based on virus-like particles (VLPs) are currently in the spotlight due to their potential for generating high immunogenic responses while presenting fewer side effects than conventional vaccines. These self-assembled nanostructures resemble the native conformation of the virus but lack genetic material. They are becoming a promising platform for vaccine candidates against several diseases due to the ability of modifying their membrane with antigens from different viruses. The coproduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 76 publications
2
14
0
Order By: Relevance
“…For example, RDIMIS identified 80 vesicle-specific binders for a population of human cell line–derived EVs and showed that the interactome of recombinant and endogenously generated EVs were remarkably similar. This is consistent with previous works showing strong similarities between the proteomic and lipid compositions of recombinant and endogenous EVs ( 26 , 46 ). Therefore, these binders may shed light on the receptor specificity of endogenous EVs and their potential signaling activity.…”
Section: Discussionsupporting
confidence: 93%
“…For example, RDIMIS identified 80 vesicle-specific binders for a population of human cell line–derived EVs and showed that the interactome of recombinant and endogenously generated EVs were remarkably similar. This is consistent with previous works showing strong similarities between the proteomic and lipid compositions of recombinant and endogenous EVs ( 26 , 46 ). Therefore, these binders may shed light on the receptor specificity of endogenous EVs and their potential signaling activity.…”
Section: Discussionsupporting
confidence: 93%
“…Further experiments would be needed to determine whether the effect is strictly due to Env expression or associated with the strain of Env (and Gag or Pol) used in these studies. Characterization of extracellular vesicles coexpressed in HEK cells once transfected with HIV-1 VLP expression vectors has shown the act of transfection is sufficient to induce morphological changes in these particles [ 110 ]. Nonetheless, these observations highlight the need for more efficient and scalable methods for the removal of contaminating particles from HIV-1 VLP immunogens in the production of potential VLP vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Primary antibodies used for protein validation were mouse anti‐HIV‐1 p24 (A2‐851‐100, Icosagen, Estonia, 1:1000), rabbit anti‐CNPase antibody (ab183500, Abcam, UK, 1:1000), rabbit anti‐CIT antibody (ab86782, Abcam, UK, 1:2000), rabbit anti‐NEDD4‐2 antibody (ab46521, Abcam, UK, 1:1000) and mouse anti‐ß‐actin antibody (MA5‐15739, Thermo Fisher Scientific, 1:5000) as a loading control. Western blots were performed following the protocol previously reported (Lavado‐García, Jorge, et al, 2020; Lavado‐García, González‐Domínguez, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%